IMPROVING NUMBER OPERATION SKILLS THROUGH FLANNEL BOARD - Hilmatuljannah (JURNAL PENDIDIKAN DAN PENELITIAN SERUMPUN MENGAJAR, 2024)
This research is motivated by the lack of ability of early childhood in number operations, so that the ability of number operations is less than optimal. Referring to this, this study aims to improve number operations in children aged 4-5 years at Hidayatul Mubtadiin PAUD. Measurement of number operation skills is calculated based on number operation indicators. This study uses class action research, there are two cycles conducted by researchers. The population of this study is early childhood 4-5 years at PAUD Hidayatul Mubtadiin totaling 15 students. With data collection techniques used in this study, namely observation, interviews and documentation. The results of this study in the use of fanel board media can improve the ability of children's number operations aged 4-5 years at Hidayatul Mubtadiin PAUD, Tunjung Teja District. Based on observations of the initial conditions of early childhood at PAUD Hidayatul Mubtadiin, Tunjung Teja District in the ability of number operations is still very lacking. The increase can be seen from the percentage of pre-action completeness of 62.88%, which increased to 70.58% in cycle I and reached 75.19% in cycle II. This research was declared successful because it had exceeded the success indicator (>75%), so the action was stopped.